Analisis Rumusan Visi, Misi, Dan Tujuan Pendidikan Anak Usia Dini di TK II Pertiwi - Zulfania, Safira (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2021)
This research wanted to know the planning of the management of the vision, mission, and goals of the school in TK II Pertiwi Semarang. Choosing this kindergarten because the school institution has the appropriate vision, mission and goals. This research is descriptive research, namely research defines how the management of the vision, mission, and goals of TK II Pertiwi Semarang. The data obtained using qualitative research, data collection techniques can be done through observation and interviews. In preparing the vision and mission, it involves elements of the surrounding community and the management of related institutions. Pertiwi Kindergarten II School based on the vision, mission and objectives already includes the existing criteria. There needs to be an evaluation if there is anything that needs to be improved.